Correlations between frequency shifts and volume changes near the λ-phase transitions in NH 4 Cl - Bas, M.; Yurtseven, H. (Springer Science and Business Media LLC, 1998)
This study gives our correlations between the volume changes and the ultrasonic frequencies of NH4Cl as a function of temperature under various pressures near the λ-phase transitions in this crystal system. We have established these correlations using the ultrasonic frequencies of the q [110] in the first-order, q [110] in the tricritical, and q [100] in the second-order phase regions for NH4Cl. We have first determined the values of Gruneisen parameter γ for each mode. We have then predicted the ultrasonic frequencies using a single γ Gruneisen parameter determined for each mode, right through the phase transition regions. For this analysis we have used the data of the literature for the ultrasonic frequencies and the length-change measurements for the first-order, tricritical and the second-order phase regions in the NH4Cl crystal. Our results show that there is quite good agreement between our calculated frequencies and the observed frequencies from the literature for the q [110] mode in the first-order and q[110] mode in the tricritical phase regions. For the q [100] mode in the second-order phase region our calculated frequencies exhibit the same critical behavior as those observed.